The impact of flash sales and brand image on purchase intention and its impact on purchase decision - Rita Rita; Denisa Natalia Guinardi (Institute of Computer Science (IOCS), 2023)
The current era of real and virtual worlds has developed rapidly, this has encouraged many industries to make changes, especially in the technology industry and sales including the marketplace. Indonesia is dominated by many marketplaces, one of the largest is Tokopedia. This study aims to find out whether there is an effect of the Flash Sale , Brand Image, program on Purchase Intention, and its impact on Purchase Decision users of D-Link products by targeting 97 respondents. This study uses the SPSS test and it is known that Flash Sale affects Purchase Intention and Purchase Decision while Brand Image affects Purchase Intention and does not affect Purchase Decision directly.